소용량 수소액화 파일럿 플랜트 구축을 위한 공정의 열역학 해석 - 김태훈(TAEHOON KIM); 최병일(BYUNG-IL CHOI); 한용식(YONG-SHIK HAN); 도규형(KYU HYUNG DO) (한국수소 및 신에너지학회 논문집, 2020)
The present study discussed the thermodynamic analysis of the hydrogen liquefaction process to build a hydrogen liquefaction pilot plant with a small capacity (0.5 ton/day). A 2-stage Brayton cycle utilizing LNG/LN2 cold energy was suggested to be built in Korea for the hydrogen liquefaction pilot plant with a small capacity. Thermodynamic analysis on the effect of various variables on the efficiency of hydrogen liquefaction process was performed. As a result, the CASE in which the ortho-para conversion catalyst was infiltrated inside the heat exchanger showed the best process efficiency. Finally, thermodynamic analysis was performed on the effect of turbo expander compression ratio on the hydrogen liquefaction process and it was confirmed that an optimal turbo expander compression ratio exists.